Peningkatan Keterampilan Menulis Melalui Strategi Kooperatif Tipe STAD - Jusniati Jusniati (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
This study aims to describe (1) planning to improve writing skill through cooperative STAD type cooperative strategy of class XII IPA 4 SMA Negeri 1 Pasangkayu Pasangkayu Regency; (2) the implementation of improving writing skill through STAD type cooperative stategi 1 IPA 4 SMA Negeri 1 Pasangkayu Pasangkayu regency, and (3) assessment improving writing skill through cooperative type STAD strategy of grade XII students IPA 4 SMA Negeri 1 Pasangkayu. This research is a type of Classroom Action Research (PTK). This research was conducted at SMA Negeri 1 Pasangkayu Pasangkayu Regency that is class XII IPA4. This research data in the form of quantitative data that is result of student writing (essay) and qualitative data collected by using instrument. The instrument of this research is test and nontes, type of test used is writing activity, while nontes in the form of observation guidance, documentation study, and interview. The result of the research shows that in improving writing skill through STAD type cooperative stategial strategy IPA 4 SMA Negeri 1 Pasangkayu Pasangkayu regency in the stage of planning, implementation, and assessment of cycle I have not maximized because of obstacles faced by teachers and students in learning. However, in the second cycle of implementation planning, and assessment can be maximized with the limitation of all the obstacles experienced in the first cycle so that students' writing skills have a good change. or increase. Thus, STAD type cooperative strategy can improve the writing skill of grade XII students IPA4 SMA Negeri 1 Pasangkayu Pasangkayu regency.